GOVERNMENT STRATEGIES TO PREVENT FARMER SUICIDES IN KARNATAKA: AN ANALYTICAL STUDY - Shree, Yamuna; Gowda, Gunde (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The issue of farmer suicides in Karnataka, India, is a big, sad problem. It's knotted up with things like money matters, community stuff, nature woes, and emotional struggles. This research project takes a good, hard look at the difficulties farmer people have to wade through in Karnataka. We're talking about monetary troubles due to heavy debts, social burdens coming from family and society's expectations, nature-related troubles like droughts and climate change, and emotional challenges that get worse with loneliness and a lack of helpful networks. The government's stepping in with a mixed bag of solutions - from debt easement steps, grants, crop insurance plans, to mental health programs. They're hoping to fix these problems and save lives. But - and you're gonna love this question - are these solutions actually working? That's what we want to find out. We should dig deep to find the real, root issues and help the farming field become strong and flexible in all ways - economic to emotional. This research points out that we seriously need a wide-ranging plan of action. It should put the well-being of farmer folks first and encourage ways of farming that are good for the long run - for Karnataka, sure, but really for the whole wide world.